1988
DOI: 10.1080/00039896.1988.10545947
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effects of Solvent Exposure on Sewage Treatment Workers

Abstract: Nineteen Sewage Treatment Workers (STWs) exposed to industrial sewage that contained benzene, toluene, and other organic solvents at a primary sewage treatment plant in New York City (Plant A) were examined for evidence of solvent toxicity. Fourteen (74%) complained of central nervous system (CNS) symptoms consistent with solvent exposure, including lightheadedness, fatigue, increased sleep requirement, and headache. The majority of these symptoms resolved with transfer from the plant. Men working less than 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
(13 reference statements)
1
22
0
1
Order By: Relevance
“…However, hydrogen sulfide levels are generally low and are unlikely to cause health effects [Melbostad et al, 1994]. A few studies mention health effects in sewage workers due to accidental or long-term exposure to other chemicals such as organic solvents and hexachlorocyclopentadiene (HCCPD), an intermediate compound in the manufacture of pesticides [Morse et al, 1979;Kraut et al, 1988]. Although health effects due to chemical exposures cannot be excluded, it is implausible that they are a main cause of symptoms in this large sample of wastewater treatment plants that receive mainly domestic wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…However, hydrogen sulfide levels are generally low and are unlikely to cause health effects [Melbostad et al, 1994]. A few studies mention health effects in sewage workers due to accidental or long-term exposure to other chemicals such as organic solvents and hexachlorocyclopentadiene (HCCPD), an intermediate compound in the manufacture of pesticides [Morse et al, 1979;Kraut et al, 1988]. Although health effects due to chemical exposures cannot be excluded, it is implausible that they are a main cause of symptoms in this large sample of wastewater treatment plants that receive mainly domestic wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, a clustering of multiple sclerosis in Galion, OH, from 1982 to 1985 was attributed to an excess concentration of heavymetal wastes, especially cadmium and chromium, in sewage and river water. 31 Kraut et al 32 reported that neurotoxic effects can be caused by chemical exposures from sewage.…”
Section: Commentmentioning
confidence: 99%
“…[1][2][3] Respiratory disorders and lung function impairments are the main health effects of exposure to bioaerosols. 4 For instance, Friis, et al, in their study demonstrated that respiratory in-a r t i c l e increase in the prevalence of respiratory symptoms (including dyspnea, bronchitis, and asthma) and decrease in pulmonary function test (PFT) parameters attributable to bio-aerosol exposure.…”
Section: Introductionmentioning
confidence: 99%